Pengaruh Penerapan Strategi Pembelajaran Aktif Critical Incident Terhadap Motivasi Belajar Siswa Pada Mata Pelajaran Aqidah Akhlaq Di Madrasah Aliyah Al Hamidiyah Kab. Pelalawan - Indra Sari, Helmaya; Afriani, Gusma; Syukri, Mahyudin (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
This research aimed at testing the effect of implementing Critical Incident learning strategy toward student learning motivation on Akidah Akhlak subject at Islamic Senior High School of Al Hamidiyah, Pelalawan Regency. It was quantitative research with quasi-experiment method and non-equivalent control group design. All students at Islamic Senior High School of Al Hamidiyah, Pelalawan Regency were the population of this research, and they were 95 students. The samples were the tenth-grade students of classes and A dan B, they were 60 students 30 students of class A as the experiment group and 30 students of class B as the control group. observation, questionnaire, test and documentation were used to collect data. Independent sample t-test was the technique of analyzing data. Based on data analysis result, there was a difference of learning motivation between students taught by using Critical Incident learning strategy and those who were taught by using Expository learning strategy on Akidah Akhlak subject at Islamic Senior High School of Al Hamidiyah, Pelalawan Regency. It was proven with tobserved higher than ttable at 5% significant level (6.030>1.671). Sig. (2-tailed) was lower than α (0.00<0.05)